[Kudyapi playing] - Philippines. National Commission for Culture and the Arts. (Manila NCCA)
A documentation on how to play the Kudyapi as demonstrated by a Ganaba awardee. Also includes an interview.
VHS.
Keywords: Filipino poetry; Musical instruments -- Philippines